Correction: Gao et al. TGF-β1 Facilitates TAp63α Protein Lysosomal Degradation to Promote Pancreatic Cancer Cell Migration. Biology 2021, 10, 597 - Guohui Gao; Jie Chen; Dongbo Wang; Qiao Li; Xiaojiao Yang; Jindan Wang; Zhiyong Pan; Zhi-Xiong Jim Xiao; Yong Yi (Biology, 2022)
In the original publication [...]